Human Сysticercosis caused by Taenia solium, Taenia crassiceps, Taenia hydatigena, Taenia martis - S. B. Chuelov; A. L. Rossina (Детские инфекции (Москва), 2022)
The urgency of the problem of human cysticercosis is due to the widespread prevalence of this disease, polymorphism and the severity of clinical manifestations. The purpose and result of the work is to summarize the available information about the etiology, epidemiology, clinical picture, diagnosis, and treatment of human cysticercosis.Conclusion. Cysticercosis affects several million people worldwide. The clinic depends on the location of the cysticercus. Diagnostics is carried out on the basis of a morphological study of the obtained biomaterial, instrumental, serological and molecular genetic research methods. Albendazole, praziquantel are used as etiotropic therapy. Surgical removal of cysticercus is performed according to indications.